2005
DOI: 10.1002/mc.20113
|View full text |Cite
|
Sign up to set email alerts
|

The feasibility of monitoring NF‐κB associated cytokines: TNF‐α, IL‐1α, IL‐6, and IL‐8 in whole saliva for the malignant transformation of oral lichen planus

Abstract: Previous investigations have demonstrated that immune activation and chronic inflammation may be one of the causes of oncogenesis. A previous study from our lab has shown significant increases of NF-kappaB dependent cytokines, TNF-alpha, IL-1alpha, IL-6, and IL-8 in different oral fluids from oral lichen planus (OLP) patients. The aim of this analysis was to explore the potential of detecting these cytokines in whole unstimulated saliva (WUS) in monitoring the malignant transformation of OLP. Thirteen patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
115
1
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 146 publications
(125 citation statements)
references
References 52 publications
(60 reference statements)
5
115
1
4
Order By: Relevance
“…An active, energy-dependant mode of transport causes difficulties in interpreting the salivary concentrations, because concentrations of salivary peptides do not always correlate as well with plasma concentrations as do concentrations of passively diffused steroids. For certain cytokines, such as tumor necrosis factor and leptin, lower concentrations appear in saliva than in plasma (10,11 ). For other cytokines, such as epidermal growth factor (12 ) and ghrelin (13 ), saliva concentrations have been observed to be equal to or higher than those in plasma.…”
Section: Transfer Of Hormones To Salivamentioning
confidence: 99%
“…An active, energy-dependant mode of transport causes difficulties in interpreting the salivary concentrations, because concentrations of salivary peptides do not always correlate as well with plasma concentrations as do concentrations of passively diffused steroids. For certain cytokines, such as tumor necrosis factor and leptin, lower concentrations appear in saliva than in plasma (10,11 ). For other cytokines, such as epidermal growth factor (12 ) and ghrelin (13 ), saliva concentrations have been observed to be equal to or higher than those in plasma.…”
Section: Transfer Of Hormones To Salivamentioning
confidence: 99%
“…A natural producer of glutamic acid E. corrodens (2) Anaerobic bacterium normally in the adult human oral cavity but that may become an opportunistic pathogen, especially in immunocompromised individuals Escherichia coli (5) One of the foremost causes of food poisoning, also found in the human digestive tract Haemophilus influenzae (13) An opportunistic pathogen involved in numerous diseases Lactococcus lactis subsp. lactis (11) Used in the dairy industry for cheese, yogurt, and buttermilk production Leifsonia xyli subsp.…”
Section: Bacillus Halodurans (3)mentioning
confidence: 99%
“…Cannot tolerate oxygen and is one of the methane-producing microbes Mycobacterium leprae (2) The bacterium that causes leprosy Mycobacterium tuberculosis (2) The major cause of tuberculosis Mycoplasma genitalium (2) Causes reproductive tract infections P. multocida (5) A pathogenic bacteria causing many serious diseases in humans and animals Porphyromonas gingivalis (8) One of the leading causes of periodontal disease…”
Section: Bacillus Halodurans (3)mentioning
confidence: 99%
See 1 more Smart Citation
“…5 Elevated levels of IL-8 in the serum of OLP patients have been recorded and reported in several studies. 6,7,8,9 It has also been reported that the clinical severity of OLP is directly associated with the IL-8 level in the serum. 9 Declaration of Interests: The authors certify that they have no commercial or associative interest that represents a conflict of interest in connection with the manuscript.…”
Section: Introductionmentioning
confidence: 97%